Peran Guru Bimbingan Konseling Mengatasi Persepsi Buruk Siswa Terhadap Layanan Bimbingan Konseling di SMKN X Kota Malang - Kirana, Desi Candra (Maliki Interdisciplinary Journal, 2024)
The role of guidance and counseling teachers is very important in coordinating guidance and counseling activities in schools. However, guidance and counseling (GC) teachers are often undervalued, and there is a negative stigma that can hinder the implementation of guidance and counseling programs in schools. This article aims to outline the roles and functions of GC teachers, address the negative perceptions towards counseling programs, and ensure the optimal utilization of the facilities provided by GC to support student learning success. The research method used is library research, with data collection techniques through archiving and content analysis. The analysis reveals that GC teachers have four main functions: understanding, prevention, alleviation, and maintenance and development. In addition, there are also functions of placement and adjustment. However, despite these functions, there remains a negative perception ingrained in students’ minds about the GC program, such as viewing counselors as school police or merely advice-givers. Therefore, this article will provide a comprehensive overview of GC teachers in enhancing the effectiveness of guidance and counseling programs in schools, with the hope of changing students’ perspectives on GC programs to a more positive one.